Optimal flip angle of Gd-EOB-DTPA-enhanced MRI in patients with hepatocellular carcinoma and liver metastasis. - Okada, Masahiro; Wakayama, Tetsuya; Yada, Norihisa; Hyodo, Tomoko; Numata, Kazushi; Kagawa, Yuki; Nishiyama, Daisuke; Miyakoshi, Keizo; Murakami, Takamichi (Abdominal Imaging, 2014)
Purpose: To investigate optimal flip angle (FA) of three-dimensional fat-suppressed T1-weighted image on Gd-EOB-DTPA-enhanced MRI.Methods: Forty-five patients with 35 hepatocellular carcinomas (HCCs) and 16 liver metastases (METs) were investigated. Signal-to-noise ratio (SNR), tumor-to-liver contrast (TLC) of HCC and MET, visual image quality (IQ) and lesion conspicuity (LeCo) were evaluated at hepatobiliary phase with different FAs (FA15°-30°-45°-60° in 13 patients, FA5°-10°-15°-20°-25° in 32 patients).Results: TLC gradually showed better in range from FA15° to FA60° and FA5° to FA25°, but SNRs gradually decreased. SNR and TLC-MET at FA15° were significantly better than those at FA45° and FA60°. SNR at FA10° was significantly higher than at FA5°, FA20°, and FA25°. TLC-HCC and TLC-MET at FA5° were inferior to other FAs. IQs and LeCos at FA15° and FA30° were superior to those at FA45° and FA60°. IQs at FA5° and FA25° were significantly lower than those at FA10°-20°, although LeCos for HCC and MET at FA25° were superior to those at FA5°-20°.Conclusions: FA ranging from 10° to 20° is suitable for hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI, to image HCC and MET.